Monitoring antibiotic resistance profiles of faecal isolates of Enterobacteriaceae and the prevalence of carbapenem-resistant isolates among food handlers in Kuwait. (June 2021) - Moghnia, Ola H.; Rotimi, Vincent O.; Al-Sweih, Noura A.
Highlights: Current status of antibiotic susceptibility of foodborne pathogens in Kuwait. High level of resistance among Enterobacteriaceae isolates from community food handlers (CFHs) was observed. Alarming level of carbapenem resistance in CFHs, suggesting dissemination of resistant isolates from healthcare settings. Determining faecal CRE carriage in the community is important to determine its epidemiology and improve infection control. Improved understanding of the epidemiology and therapeutic options for CRE will aid in better infection control strategies. ABSTRACT: Objectives: Carbapenem-resistant Enterobacteriaceae (CRE) have become one of the most challenging problems in infectious diseases worldwide. Unrecognised personnel such as food handlers (FHs) colonised with CRE serve as a reservoir for transmission. This study assessed the prevalence and susceptibility patterns of CRE isolates from FHs working in commercial eateries in the community (CFHs) and healthcare settings (HCFHs) in Kuwait over the period 2016–2018. Methods: Representative colonies from faecal samples were identified by API 20E and a VITEK®2 ID System. Susceptibility testing against 21 antibiotics was performed by Etest and agar dilution. Results: A total of 681 isolates of the family Enterobacteriaceae were isolated from 405 FHs, of which 425 (62.4%) were Escherichia coli and 126 (18.5%) were Klebsiella pneumoniae . The prevalence of CRE among FHs was 7.7% (31/405), comprising 32% CFHs (10/31) and 68% HCFHs (21/31). Ampicillin, tetracycline and cefalotin showed very poor activities against most isolates with resistance rates of 63.3%, 41.7% and 40.8%, respectively. The prevalence of multidrug-resistant (MDR) isolates was 30.5%, including 130 E. coli (30.6%) and 22 K. pneumoniae (17.5%). An alarming level of colistin resistance (11.3%) was noted. A significant proportion of FH isolates (13.2%) exhibited extended-spectrum β-lactamases (ESBL) phenotypes, including 80 E. coli (18.8%) and 5 K. pneumoniae (4.0%). Conclusion: This study revealed that asymptomatic intestinal carriage of CRE, including MDR and ESBL isolates, was relatively common in our community. It is conceivable that FHs may pose a significant risk to consumers for the acquisition and spread of resistant strains.